Morbidity, Cost and Role of Health Care Worker Transmission in an Influenza Outbreak in a Tertiary Care Hospital - Annalee Yassi; Myrna McGill; Donna Holton; Lindsay Nicolle (Canadian Journal of Infectious Diseases)
An influenza A outbreak involving 17 health care workers (HCWs) and 16 chronic geriatric patients on a ward in a tertiary care hospital was reviewed. Thirty-seven per cent of all HCWs and 47% of patients on the affected wards became ill with influenza. Three patients died during the outbreak. The majority of health care workers became ill prior to detecting the first patient case of influenza, suggesting that nosocomial spread from HCWs to patients may have occurred. Only 13.7% of the staff and 5.9% of the patients had been vaccinated prior to the outbreak. Lost time due to HCW absenteeism, outbreak-related medication costs and additional staff time involved in outbreak control resulted in considerable cost to the hospital. It is suggested that much of this cost, as well as morbidity and possibly mortality, could have been avoided by increased immunization of HCWs and patients.